Online 8-week cognitive therapy for problem gamblers: The moderating effects of depression symptoms and perceived financial control - Palomäki Jussi Petteri; Heiskanen Maria; Castrén Sari (AKADEMIAI KIADO ZRT, 2025)
Background and aims:
Online interventions for problem gambling are increasingly popular, but not everyone benefits from them. We describe 12 years of real-world data from an online intervention for gambling problems and aim to find out the extent to which depression, alcohol use, and sense of financial control influence the effectiveness of the program.
Methods:
We analyzed treatment effectiveness and moderators in the Finnish "Peli Poikki" program (2007-2018)-an 8-week cognitive behavioral therapy and follow-up program for problem gambling. Participants were Finnish-speaking adults over 18 years of age (N = 2011, 66.9% males). We measured the self-reported level of problem gambling, depression, alcohol use, and sense of financial control across four treatment phases (baseline, post-treatment, 6-month follow-up, and 12-month follow-up), as well as the presence of gambling debt, psychological and physiological health, years suffered from gambling problems, and demographic variables.
Results:
Participation grew across years with retention rates of 55%, 30%, and 19% for post-treatment and the two follow-ups, respectively. The average problem gambling scores declined significantly following treatment and remained low throughout the follow-ups. However, this decline (the beneficial treatment effect) was reversed after the follow-ups for those with high depression scores and those who felt they had no control over their finances.
Discussion and Conclusions:
The Peli Poikki program is a well-functioning online intervention but less effective in the long term for participants with persisting symptoms of depression or without a sense of financial control. More attention is needed to screen and direct people with comorbidities to the appropriate services.